Students’ risks for out-of-school suspensions: indigenous heritage and child protective services involvement - Cho, Minhae (Child maltreatment, 2023)
Disproportionality in out-of-school suspensions (OSS) is a persistent social and racial justice issue. Available research indicates that Indigenous children are disproportionately represented in both OSS and the child protective services (CPS) system. This secondary data analysis followed a cohort of 3rd grade students (n = 60,025) in Minnesota public schools from 2008- 2014. It examined the relationship between CPS involvement, Indigenous heritage, and OSS. Results from a zero-inflated negative binomial regression indicated that Indigenous students had two times the odds of suspension compared to white students (OR = 2.06, p < .001). Furthermore, there was a significant interaction between CPS involvement and Indigeneity on frequency of OSS (OR = 0.88, p < .05). Indigenous students showed a much higher odds ratio of OSS compared to white students, but the distance between the odds ratios of the two groups decreased as the number of child maltreatment allegations increased. Indigenous students may experience relatively high levels of both CPS and OSS due to systematic racism. We discussed implications for practice and policy to reduce discipline disparities.